Stock market performance and COVID-19 pandemic: evidence from a developing economy. Issue 1 (14th January 2021) - Insaidoo, Michael; Arthur, Lilian; Amoako, Samuel; Andoh, Francis Kwaw
Abstract : Purpose: The purpose of this study is to assess the extent to which the Ghana stock market performance has been impacted by the novel COVID-19 pandemic. Design/methodology/approach: The study used the exponential generalized autoregressive conditional heteroscedasticity (EGARCH) model, by using daily time series data from 2 January 2015 to 13 October 2020. Both pre-estimation (Augmented Dickey-Fuller and Phillips-Perron) and post-estimation tests (Jarque-Bera) were conducted to validate the results. Findings: While the study shows a statistically insignificant negative relationship between the COVID-19 pandemic and the Ghana stock returns, the results confirm that the COVID-19 pandemic has occasioned an increase in the Ghana stock returns volatility by 8.23%. Furthermore, the study confirmed the presence of volatility clustering and asymmetric effect, with the latter implying that worthy news tends to affect volatility more than unwelcome news of equal size. Practical implications: To dampen uncertainties that trigger stock market volatility, the government should surgically target worse affected COVID-19 pandemic businesses and households to check the drop in profits and demand. Rigidities associated with stock market operations must be addressed to make it attractive to investors even in the midst of a pandemic. Originality/value: This paper is a pioneer attempt at assessing the extent to which a developing economy stock market has been impacted by the novel COVID-19 pandemic using the EGARCH model.